Causes of persistent rural poverty in Thika district of Kenya, c.1953-2000 - Kinyanjui, Felistus Kinuna (Rhodes University, Faculty of Humanities, Department of History, 2007)
This study investigates the causes of poverty among the residents of Thika District in Kenya over the period 1953-2000. Using the articulation of modes of production perspective, the study traces the dynamics of poverty to the geography, history and politics of Thika District. The thrust of the argument is that livelihoods in the district changed during the period under investigation, but not necessarily for the better. Landlessness, collapse of the coffee industry, intergenerational poverty, and the ravages of diseases (particularly of HIV/AIDS) are analysed. This leads to the conclusion that causes of poverty in Thika District during the period under examination were complex as one form of deprivation led to another. The study established that poverty in Thika District during the period under review was a product of a process of exclusion from the centre of political power and appropriation. While race was the basis for allocation of public resources in colonial Kenya, ethnicity has dominated the independence period. Consequently, one would have expected the residents of Thika District, the home of Kenya's first president, Mzee Jomo Kenyatta, to have benefited inordinately from public resources during his rule. Kenyatta's administration, however, mainly benefited the Kikuyu elite. The study therefore demonstrates that during the period under examination, the Kikuyu, like any other Kenyan community, were a heterogeneous group whose differences were accentuated by class relations. Subaltern groups in Thika District therefore benefited minimally from state patronage, just like similar groups elsewhere in rural Kenya. By the late 1970s, the level of deprivation in rural Kenya had been contained as a result of favourable prices for the country's agricultural exports. But in the subsequent period, poverty increased under the pressures of world economic recession and slowdowns in trade. The situation was worse for Kikuyu peasants as the Second Republic of President Daniel Moi deliberately attempted undermine the Kikuyu economically. For the majority of Thika residents, this translated into further marginalisation as the Moi regime lumped them together with the Kikuyu elite who had benefitted inordinately from public resources during the Kenyatta era. This study demonstrates that no single factor can explain the prevalence of poverty in Thika District during the period under consideration. However, the poor in the district devised survival mechanisms that could be replicated elsewhere. Indeed, the dynamics of poverty in Thika District represent a microcosm not just for the broader Kenyan situation but also of rural livelihoods elsewhere in the world. The study recommends land reform and horticulture as possible ways of reducing poverty among rural communities. Further, for a successful global war on poverty there is an urgent need to have the West go beyond rhetoric and deliver on its promises to make poverty history.
Keywords: Poverty -- Kenya -- History; Rural poor -- Kenya -- History; Agriculture -- Kenya -- History; Kenya -- History; Kenya -- Politics and government